Vitamin, sterol and fatty acid contents of some edible and medicinal plants from East and Southeast Anatolia (Turkey) - Keser, Serhat; Celik, Sait; Turkoglu, Semra; Yilmaz, Ökkes; Turkoglu, Ismail (Turkish Pharmacists Association, 2015)
Achillea millefolium L., Crataegus monogyna subsp. monogyna Jacq., Rubus discolor L., Salvia multicaulis Vahl., Morus alba L. and Pistacia terebinthus L. plants are consumed for some medicinal or nutritional purposes. The chemical composition, vitamins, sterols and fatty acid contents of these plants were presented in this study. Vitamin and sterol contents were high in A. millefolium flowers in comparison to leaves and seed. Vitamins E, K, and total sterol levels in C. monogyna subsp. monogyna fruit were higher than leaves and flower. For R. discolor fruit; vitamin and sterol contents were higher than leaves, flower and unripe fruit. For S. multicaulis, vitamin content was higher in leaves and the sterol content was higher in seed than other extracts. ?-Tocopherol, vitamins K, D and total sterol levels in M. alba fruit were higher than leaves and unripe fruit. In P. terebinthus, retinol and ?-tocopherol levels were higher in leaves, vitamins D, K, sterol levels were higher in flower than other extracts. The present study indicates that these plants can be a good natural source of fatty acids, vitamins and sterols. This study is first report about the phytochemical properties of R. discolor, and S. multicaulis. © 2015, Turkish Pharmacists Association. All rights reserved.
Doğu ve güneydoğu anadolu’da (Türkiye) yetişen bazı yenebilir ve tıbbi bitkilerin vitamin, sterol ve yağ asidi içerikleri
Keywords: Blackberry; Fatty acid; Hawthorn; Mulberry; Sterol; Vitamin; Yarrow